DETERMINATION OF METAZACHLOR RESIDUES IN WINTER OILSEED RAPE (BRASSICA NAPUS VAR. XENON) BY HPLC - Koleva-Valkova, Lyubka; Vasilev, Andon; Dimitrova, Maya; Stoychev, Dimitar (Emirates Journal of Food and Agriculture, 2016)
Rape is the main oilseed crop grown in many countries around the world. The seeds are used in the food industry for extraction of oil, as livestock feed or for production of biofuels. The high yield production requires the application of herbicides. The most commonly used herbicide in the cultivation of rape is Butisan S with active substance metazachlor. Often in adverse weather conditions the active substance enters the rape plants, causing a number of disturbances in the physiology-biochemical processes, but also represents a real risk of contamination of the yield. In the present study residues of metazachlor were identifi ed in samples of rape variety Xenon after soil application of the herbicide Butisan S at dose of 200 ml/da. The highest concentration (14,6 μg/g FW) was recorded in leaves 28 days after treatment with the herbicide. The concentration of metazachlor in rape plants decreased in time, with values of 4,4 μg/g FW at 48 days after treatment and 1,23 μg/g FW at 68 days. In foliar application of the herbicide the detected residues of metazachlor in leaves were lower with 4,24 μg/g FW on day 8 and 0,95 μg/g FW 20 days after treatment. The highest yield was recorded in the variant with soil application (200 ml/da) of the herbicide (yield 2683 kg/ha) as compared to the control (without herbicide application) (yield 1683 kg/ha).